Arthroscopic Posterior Articular Coverage and Shift (PACS) Procedure for Treatment of Preosteoarthritic Constitutional Static Posterior Shoulder Instability (Type C1). Issue 13 (November 2022) - Moroder, Philipp; Gebauer, Henry; Paksoy, Alp; Siegert, Paul; Festbaum, Christian; Rüttershoff, Katja; Lacheta, Lucca; Thiele, Kathi; Akgün, Doruk
Background: Different joint-preserving techniques for treatment of preosteoarthritic, constitutional static (type C1) posterior shoulder instability (PSI) have been proposed, including posterior glenoid open wedge osteotomy and bone graft augmentation. However, the techniques are demanding, the reported complication and reoperation rates are high, and posterior decentering cannot reliably be reversed. Purpose: To assess the clinical and radiological longitudinal outcomes of patients with type C1 PSI after arthroscopic posterior articular coverage and shift (PACS) surgery. Study Design: Case series; Level of evidence, 4. Methods: We performed a retrospective analysis of a prospective database with longitudinal follow-up including 14 shoulders in 13 patients who underwent an arthroscopic PACS procedure for symptomatic preosteoarthritic constitutional static posterior instability (type C1) with previous failed nonoperative treatment. Patients were clinically evaluated before surgery and at 3, 6, 12, and 24 months postoperatively in terms of satisfaction and pain levels as well as standardized physical examination, Subjective Shoulder Value (SSV), Western Ontario Shoulder Instability Index (WOSI) score, Constant score, and Rowe score. Preoperative, postoperative, and follow-up magnetic resonance imaging scans were obtained in all patients. A paired 2-sample t test was used to compare changes in continuous variable parameters over time. Correlation analyses were performed using the Pearson correlation coefficient. Results: All outcome scores and the pain level improved significantly from preoperatively to postoperatively, and the improvement was sustained over the follow-up period of 2 years (pain level, 6.4 preoperatively vs 3.3 at 2 years, P < .001; SSV, 40 vs 70, P = .001; WOSI, 33 vs 56, P = .001; Constant, 70 vs 79, P = .049; Rowe, 52 vs 76, P < .001). The mean glenohumeral and scapulohumeral subluxation indices were significantly lower in the early postoperative period compared with preoperative measurements (glenohumeral, 52% ± 6% vs 58% ± 10%, P = .02; scapulohumeral, 70% ± 8%; vs 77% ± 9%, P = .002, respectively); however, they returned to baseline values at follow-up (57% ± 7% vs 58% ± 10%, P = .7; 75% ± 6% vs 77% ± 9%, P = .4, respectively). A high scapulohumeral subluxation index, excessive glenoid retroversion, and increased posterior positioning of the humeral head in relation to scapular blade axis and older age were correlated with worse clinical outcomes. Conclusion: Over the follow-up period of 2 years, the PACS procedure significantly improved outcome scores in patients who had preosteoarthritic constitutional static posterior shoulder instability, especially in younger patients with less severe glenoid retroversion and posterior decentering of the humeral head. However, similar to other techniques, the PACS procedure needs to be considered a symptomatic therapy that does not reverse the underlying cause or stop the progressive pathology.